Analisis Jaringan Sosial Yang Terbangun dalam Komunitas Bikers Subuhan di Kota Tanjungpinang - Isyandi, Ari; Rahmawati, Nanik; Solina, Emmy (Jurnal Ilmu Sosial dan Humaniora, 2023)
This study aims to find out how social networks are built in the Subuhan biker community, as well as what are the external and internal factors that strengthen the Subuhan biker network. The theory used in this study is Fukuyama's social network theory, to see how social networks exist in the Subuhan biker community. This research was conducted with a qualitative approach with a descriptive type. Research informants were selected using a purposive sampling technique and in collecting data used observation and in-depth interview techniques. This study found that there are two forms of social networks in the Subuhan biker community. The first is a social network based on interests. The dawn bikers community is a motorcycle community that is religious in nature where people from all walks of life can join the community. Both social networks are based on emotional ties. Starting from their love for motorcycles while preaching, then developed into a desire to introduce their community to the public, that this motorcycle community has a different purpose from other motorcycle communities. into two, namely internal and external factors, internal factors that influence, namely the existence of the same motives, strong solidarity and group norms, while the external factor is the existence of cooperation with the government.